Isolation of Structurally Heterogeneous TCR‐CD3 Extracellular Vesicle Subpopulations Using Caliper Strategy. (27th March 2023) - Yin, Wen; Chen, Haitian; Cai, Jianye; Huang, Xing; Zhang, Lang; Xu, Yuzhi; Zheng, Jun; Liu, Si‐Yang; Zou, Xiaoyong; Dai, Zong; Yang, Yang
Abstract: Cells in different states can release diverse types of extracellular vesicles (EVs) that participate in intracellular communication or pathological processes. The identification and isolation of EV subpopulations are significant to explore their physiological functions and clinical value. In this study, structurally heterogeneous T‐cell receptor (TCR)‐CD3 EVs were proposed and verified for the first time using a caliper strategy. Two CD3‐targeting aptamers were designed in the shape of a caliper with an optimized probe distance and were assembled on gold nanoparticles (Au‐Caliper) to distinguish TCR‐CD3 monomeric and dimeric EVs (m/dCD3 EVs) in skin‐transplanted mouse plasma. Phenotyping and sequencing analysis revealed clear heterogeneity in the isolated m/dCD3 EVs, providing the potential for mCD3 EVs as a candidate biomarker of acute cellular rejection (ACR) and holding great prospects for distinguishing EV subpopulations based on protein oligomerization states. Abstract : The existence of extracellular vesicles (EVs) with different T‐cell receptor (TCR)‐CD3 oligomerization states has been verified by a proposed caliper strategy. Using a caliper probe with an optimized spacing of 16 nm, the strategy successfully isolated TCR‐CD3 monomeric EVs (mCD3 EVs) and TCR‐CD3 dimeric EVs (dCD3 EVs) from the plasma of a skin transplantation mouse model. Phenotypic analysis confirmed dCD3 EVs as a candidate biomarker for acute cellular rejection.